ANALISIS LITERATUR TERHADAP STRUKTUR DAN GENRE MIKRO DALAM TEKS PROPOSAL IMPLIKASI TERHADAP PEMBELAJARAN BAHASA INDONESIA - Aginta; Gadiza Tsalsa Kamil Batubara, Stevani Angelika Manurung; Angel Laura Siregar, Anggi Elisa Sihombing; Revalina Harahap, Muhammad Anggie Januarsyah Daulay (STKIP Subang, 2025)
Writing a scientific proposal is a crucial stage in student learning, yet many students face difficulties in structuring it. A literature review shows that research proposals are typically structured systematically with main chapters (Introduction, Literature Review, Research Methods) and additional components such as a research schedule and bibliography. The introduction of the proposal contains the background, problem statement, objectives, and benefits of the research, while the literature review section summarizes relevant previous studies. The Methods section contains the type of research, location and time, data sources, and data collection and analysis techniques. Several Indonesian studies also emphasize the importance of schedule and budget components in proposals. This study compares findings from various Indonesian language education journals to clarify the structure and micro-genres of student proposal texts. The results confirm the uniformity of the macro-structure of scientific proposals while highlighting variations in micro-genres within each section. Implications of this research include encouraging proposal writing instruction that focuses on mastering the structural framework and the appropriate use of micro genres.